Four new lanthanide–organic frameworks: selective luminescent sensing and magnetic properties. Issue 32 (28th July 2016) - Ning, Yan; Wang, Lu; Yang, Guo-Ping; Wu, Yunlong; Bai, Nannan; Zhang, Wenyan; Wang, Yao-Yu
Abstract : Four new isostructural lanthanide–organic frameworks have been synthesized, which show 2D layer-by-layer structures, and exhibit highly selective and efficient luminescence sensing for Fe 3+ and Cr 6+ ions in aqueous solution. Abstract : Four new isostructural lanthanide–organic frameworks, [Ln(L)(H2 O)2 ]·H2 O·CH3 CN (1-Ln ) (Ln = Eu, Tb, Dy, and Gd), have been successfully synthesized via solvothermal reactions with a semi-rigid V-shaped multicarboxylate ligand 2-(2′, 4′-dicarboxylphenoxy) benzoic acid (H3 L) and Ln(NO3 )3 ·6H2 O.1-Ln shows 2D layer-by-layer frameworks with interlayer channels decorated by carboxylate groups.1-Eu exhibits excellent luminescence properties, and therefore, is chosen as a probe for sensing different metal ions and anions. Consequently, 1-Eu displays high selectivity and sensitivity for Fe 3+ and Cr 6+ ions, simultaneously, through the luminescence quenching effect, and thus, should be an excellent candidate for probing these pollutant metal ions. In addition, antiferromagnetic exchange interactions also exist between the Dy 3+ ions in1-Dy .